2022
DOI: 10.1002/pbc.29910
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of texture analysis of the primary tumour in high‐risk neuroblastoma: An 18F‐DOPA PET study

Abstract: Purpose To evaluate the prognostic value of texture analysis of the primary tumour with 18fluorine‐dihydroxyphenylalanine positron emission tomography/X‐ray computed tomography (18F‐DOPA PET/CT) in patients affected by high‐risk neuroblastoma (HR‐NBL). Methods We retrospectively analysed 18 patients with HR‐NBL, which had been prospectively enrolled in the course of a previous trial investigating the diagnostic role of 18F‐DOPA PET/CT at the time of the first onset. Texture analysis of the primary tumour was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…On the other hand, Histogram_Entropy measures the randomness of voxel distribution and has been established as an important biomarker reflecting heterogeneity in various MRI and PET studies ( 43 , 45 ). In accordance with previous studies ( 40 , 42 ), we found that high rad-risk, defined as patients with both a high GLRLM_RLNU and a high Histogram_Entropy, indicating a high intratumor heterogeneity, was the most significant independent factor for EFS after adjusting for clinicopathological factors.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, Histogram_Entropy measures the randomness of voxel distribution and has been established as an important biomarker reflecting heterogeneity in various MRI and PET studies ( 43 , 45 ). In accordance with previous studies ( 40 , 42 ), we found that high rad-risk, defined as patients with both a high GLRLM_RLNU and a high Histogram_Entropy, indicating a high intratumor heterogeneity, was the most significant independent factor for EFS after adjusting for clinicopathological factors.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study reported that high intratumor metabolic heterogeneity on 18 F-FDG PET/CT was a strong prognostic factor in 38 children with newly diagnosed neuroblastoma (40), and it was the first report identifying metabolic heterogeneity as a prognostic biomarker of neuroblastoma. The authors used the area under the curve of the cumulative SUV-volume histograms (AUC-CSHs), which is a histogram-based first-order feature that describes the percentage associated with metastatic burden and had certain prognostic value (42). In the current study, we further expanded that intratumor heterogeneity was a prognostic biomarker in neuroblastoma, with a much larger cohort and a higher order of texture analysis, which further improves quantitative histogram approaches by introducing the spatial dimension.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, there are only a few studies investigating the prognostic value of PET textural features measuring tumor heterogeneity in neuroblastoma patients. According to the study of Fiz et al, 8 18F-dihydroxyphenylalanine PET textural parameters describing heterogeneity and metabolic intensity of the primary high-risk neuroblastoma were closely associated with its overall metastatic burden. Unlike this study, we examined the 18F-FDG PET texture features instead of 18F-dihydroxyphenylalanine PET.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that intratumoural metabolic heterogeneity is correlated with treatment failure, the higher possibility of metastasis, and poor prognosis in various tumors, such as lung cancer, breast cancer, and cervical cancer 7 . However, there are not many studies investigating the prognostic value of intratumor metabolic heterogeneity on 18F-FDG PET/CT in high-risk neuroblastoma patients 8 …”
mentioning
confidence: 99%